Churg-Strauss Syndrome: A Case Resembling Erythema Multiforme: Differential Diagnosis - Cicek, Demet; Kandi, Basak; Demir, Betuel; Turgut, Teyfik; Dagli, Ferda (Ortadogu Ad Pres & Publ Co, 2008)
A 44-year-old female patient presented to our outpatient clinic with breathing difficulty, abdominal pain, articular pain and skin eruptions. Her story included bronchial asthma, for which she has been monitored for 10 years. The patient was diagnosed as Churg-Strauss syndrome (CSS) based on clinical, laboratory and histopathological findings. Treatment with corticosteroid 60 mg/day was initiated. The patient's lesions improved after the treatment.
2nd Edge Dermatology Days Conference -- 2006 -- Fethiye Mugla, TURKEY
Keywords: Churg-Strauss Syndrome; erythema multiforme